1998
DOI: 10.1182/blood.v91.6.1924
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation Signaling and Activation of Shc, p21Ras, and Myc Via Tyrosine 764 of Human Granulocyte Colony-Stimulating Factor Receptor

Abstract: The membrane-distal region of the cytoplasmic domain of human granulocyte colony-stimulating factor receptor (G-CSF-R) contains four conserved tyrosine residues: Y704, Y729, Y744, and Y764. Three of these (Y729, Y744, and Y764) are located in the C-terminal part of G-CSF-R, previously shown to be essential for induction of neutrophilic differentiation. To determine the role of the tyrosines in G-CSF–mediated responses, we constructed tyrosine-to-phenylalanine (Y-to-F) substitution mutants and expressed these i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…It has been shown that truncation of the carboxy terminal region of the G-CSF-R, as seen in some patients with AML/ SCN, resulted in enhanced and prolonged Stat5 activation in response to G-CSF [7]. This region contains three tyrosine residues, i.e., Tyr 729, Tyr 744, and Tyr 764, which are involved in regulating cell proliferation and differentiation [23,26,27]. To investigate whether the carboxy terminal tyrosine residues have a role in modulating G-CSF-stimulated Stat5 activation, we expressed a series of tyrosine-to-phenylalanine substitution mutants of the G-CSF-R ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that truncation of the carboxy terminal region of the G-CSF-R, as seen in some patients with AML/ SCN, resulted in enhanced and prolonged Stat5 activation in response to G-CSF [7]. This region contains three tyrosine residues, i.e., Tyr 729, Tyr 744, and Tyr 764, which are involved in regulating cell proliferation and differentiation [23,26,27]. To investigate whether the carboxy terminal tyrosine residues have a role in modulating G-CSF-stimulated Stat5 activation, we expressed a series of tyrosine-to-phenylalanine substitution mutants of the G-CSF-R ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The cDNAs encoding the different tyrosine-to-phenylalanine substitution mutants of the G-CSF-R (kindly provided by Dr. Ivo P. Touw, Erasmus University, Rotterdam) were cloned in the pBabe-puro retroviral expression vector as described [23]. 32D cells were transfected by electroporation and selected in medium containing puromycin (1 g/ml), 24 h after transfection.…”
Section: Stable Transfectionmentioning
confidence: 99%
“…Ba/F3 cells and 32D.cl8.6 cells, a subline of the IL-3-dependent murine myeloid 32Dcl3 cell line that lacks endogenous G-CSFR (de Koning et al, 1998), were maintained in RPMI-1640 medium supplemented with 10% fetal calf serum (FCS), 100 IU/ml penicillin, 100 mg/ml streptomycin and murine IL-3 (10 ng/ml) at 371C and 5% CO 2 . To obtain Ba/F3 cells expressing wt or mutant G-CSFR, cells were electroporated as described (de Koning et al, 1996).…”
Section: Cell Culture Transfection Retroviral Transduction and Intrmentioning
confidence: 99%
“…Similar to most cytokine receptors, G-CSFR activates multiple signaling pathways fuelled by activation of JAK kinases. For instance, JAK-phosphorylated tyrosine-based motifs become docking sites for SH2-containing signaling molecules, such as signal transducer and activator of transcription (STAT) 3 (Ward et al, 1999a;Shao et al, 2006), components of the p21 Ras /Raf/MAPK pathway (Rausch and Marshall, 1997;de Koning et al, 1998) and suppressor of cytokine signaling 3 (SOCS3) (Hortner et al, 2002;Hermans et al, 2003). In addition, the membrane-proximal cytoplasmic region of G-CSFR is involved in the activation of protein kinase B (PKB), a serine/threonine kinase implicated in cell survival and in the activation of STAT5 (Dong and Larner, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…G-CSF binds a high-affinity receptor, the G-CSFR, on myeloid progenitor cells and granulocytic precursors, resulting in activation of multiple signaling intermediates including Erk1/2, the Src-related kinase Lyn, and Jak-STAT proteins [11][12][13][14][15][16][17]. STAT3 is a predominant signaling molecule stimulated by the activated G-CSFR; hence, its function in granulopoiesis has been investigated in murine models.…”
Section: Introductionmentioning
confidence: 99%